2022
DOI: 10.3390/biomedicines10071641
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response in Regard to Hypersensitivity Reactions after COVID-19 Vaccination

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes coronavirus disease 2019 (COVID-19), is a member of the genus Betacoronavirus. This virus was first detected in December 2019, and the situation quickly escalated to cause a global pandemic within a few months. COVID-19 had caused more than 5.5 million deaths as of January 2022. Hence, the urgency of effective vaccination contributed to the fastest rate of vaccine development seen to date (i.e., within 1.5 years). Despite repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Serious adverse events, including thromboembolic events, stroke, myocardial infarction, and sudden death, have been reported in rare cases following COVID-19 vaccination [ 16 , 17 ]. Although the incidence of such events remains low, the underlying causality is unclear.…”
Section: Covid-19 Prevention Vaccination: Rare Adverse Events and Cau...mentioning
confidence: 99%
“…Serious adverse events, including thromboembolic events, stroke, myocardial infarction, and sudden death, have been reported in rare cases following COVID-19 vaccination [ 16 , 17 ]. Although the incidence of such events remains low, the underlying causality is unclear.…”
Section: Covid-19 Prevention Vaccination: Rare Adverse Events and Cau...mentioning
confidence: 99%
“…Polyethylene glycol (PEG) and polysorbate 80 (PS80) were therefore identified as causal allergens contained in mRNA and viral vector-based vaccines, respectively [ 2 , 11 , 12 , 13 , 14 , 15 , 16 ]. Polysorbate 80 (PS80) is a non-ionic detergent used to solubilize proteins and is present in viral vector COVID-19 vaccines (i.e., Janssen/J&J Ad26.COV2.S and Oxford/AstraZeneca ChAdOx1-S) [ 17 ]. However, mRNA vaccines contain the mRNA encoding for the full-length SARS-CoV-2 spike (S) protein [ 18 ], protected and encapsulated within lipid nanoparticles (LNPs).…”
Section: Introductionmentioning
confidence: 99%
“…The allergological work-up programs for the evaluation of the allergic potential of allergens contained in COVID-19 vaccines were mainly focused on PEGs, given that in Italy, as in many other countries, the viral vector-based vaccines were withdrawn from the market [ 24 ]. For these reasons, the most widely used allergological work-up program for the evaluation of COVID-19 vaccine allergies included the administration of a skin prick test (SPT) with PEG-containing products; an intradermal test (IDT) and sIgE evaluation were also applied [ 17 , 25 , 26 ]. Notably, it has been demonstrated that, in this context, the reproducibility of the SPT test is time-dependent and reactivity will decline over time [ 24 ].…”
Section: Introductionmentioning
confidence: 99%